A Free man - Sethi, Aman (India Random House India, 2011)
Mohammed Ashraf has studied biology in college, and after college has learnt how to repair television sets, cut suit lengths, and slice chicken. He has lived in Mumbai, Calcutta, Hyderabad, Surat, and Patna, but this evening he is stoned on a street in Sadar Bazaar, in North Delhi. The morning shall bring hangovers, whiskey breakfasts, and possibly answers to the lingering questions that haunt Ashraf. How did he get here? Why is he the way he is? And is there a way back home? In this compelling account of the life of an itinerant labourer, Aman Sethi brings Ashraf vividly alive and illuminates the lives of countless others like him. Wry, humourous, and insightful, A Free Man is an unforgettable portrait of an invisible man in his invisible city.
Include Epilogue.
Keywords: India--Delhi -- Social Conditions